Melatonin as a Potential Neuroprotectant: Mechanisms in Subarachnoid Hemorrhage-Induced Early Brain Injury - Xu, Chengyan; He, Zixia; Li, Jiabin (Frontiers in Aging Neuroscience, 2022)
Subarachnoid hemorrhage (SAH) is a common cerebrovascular disease with high mortality and disability rates. Despite progressive advances in drugs and surgical techniques, neurological dysfunction in surviving SAH patients have not improved significantly. Traditionally, vasospasm has been considered the main cause of death and disability following SAH, but anti-vasospasm therapy has not benefited clinical prognosis. Many studies have proposed that early brain injury (EBI) may be the primary factor influencing the prognosis of SAH. Melatonin is an indole hormone and is the main hormone secreted by the pineal gland, with low daytime secretion levels and high nighttime secretion levels. Melatonin produces a wide range of biological effects through the neuroimmune endocrine network, and participates in various physiological activities in the central nervous system, reproductive system, immune system, and digestive system. Numerous studies have reported that melatonin has extensive physiological and pharmacological effects such as anti-oxidative stress, anti-inflammation, maintaining circadian rhythm, and regulating cellular and humoral immunity. In recent years, more and more studies have been conducted to explore the molecular mechanism underlying melatonin-induced neuroprotection. The studies suggest beneficial effects in the recovery of intracerebral hemorrhage, cerebral ischemia-reperfusion injury, spinal cord injury, Alzheimer's disease, Parkinson's disease and meningitis through anti-inflammatory, antioxidant and anti-apoptotic mechanisms. This review summarizes the recent studies on the application and mechanism of melatonin in SAH.